ACUTE EFFECT OF CONTINUOUS RUNNING ON WHITE BLOOD CELL (WBC) AMONG PHYSICALLY TRAINED BOYS - Ghosh, Arnab (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Introduction: In this research, the examination of the acute effect of continuous running on the white blood cell status of physically trained boys has been aimed. Methods: Ten (10) physical education male students with an average age of 23.16±1.85 years participated in this study voluntarily. The white blood cell status (WBC) of the students was analyzed before running (BR) and just after 35 minutes of continuous running (AR). To determine White blood cell status (WBC), blood samples with 5 ml EDTA were taken from the forearm ante-cubical area before and after resistance exercise, and analyzed in the laboratory using an auto-analyzer (Sysmex XP- 100). Result: Measurement results were presented as average and standard deviation. Student T-test for dependant samples was used to make a comparison between BR and AR values. P<-0.01 value was considered to be significant. The result of the study revealed that, the increase in AR than BR values for White blood cell status (WBC) was significant. Conclusion: Conclusively White blood cell status (WBC) displayed significant incensement in relation to acute continuous running.